Materials for high-temperature fuel cells - Jiang, San Ping; Yan, Yushan (Wiley-VCH, 2013)
There are a large number of books available on fuel cells; however, the majority are on specific types of fuel cells such as solid oxide fuel cells, proton exchange membrane fuel cells, or on specific technical aspects of fuel cells, e.g., the system or stack engineering. Thus, there is a need for a book focused on materials requirements in fuel cells. Key Materials in High-Temperature Fuel Cells is a concise source of the most important and key materials and catalysts in high-temperature fuel cells with emphasis on the most important solid oxide fuel cells. A related book will cover key mater.
Edition statement from running title area.
Keywords: Fuel cells -- Materials.; elektronické knihy; electronic books